The Operational Guide - for the making markets work for the poor (M4P) approach (Second Edition) - Centre, The Springfield (SDC & DFID, 2015)
In 2008, SDC and DFID published three documents aimed at improving the understanding and use of the Making Markets Work for the Poor (M4P) a pproach: the M4P Synthesis, M4P Perspectives and M4P Operational Guide . Since then the field has grown, diversified and, importantly, learne d much more. A second edition was commissioned to capture that learnin g, maintain the momentum and realise the ambition that development can still 'do better'. The second edition provides an accessible resource to help practitioners put the market systems development approach int o practice. It explains the key principles and frameworks which guide effective intervention in – and development of – market systems. It ad dresses common challenges with examples of good practice based on prac titioner experience. Who is it for? The Operational Guide is for peopl e whose job entails trying to make market systems work better for poor women and men. These people include: Individuals currently involved i n funding or implementing the approach. Development agencies wishing t o incorporate market systems thinking and practice in their work. Nati onal stakeholders that wish to play a more strategic and catalytic rol e within market systems. What is new? Application, application, applic ation! Whilst the key principles and frameworks will be familiar, the advice on their operational application – from start to finish – has b een significantly bolstered Enhanced guidance on facilitation. Greater emphasis on what constitutes good facilitation practice, building on a wealth of practitioner experience More real-life examples. The Opera tional Guide is laced with examples from programmes past and present, working in a diverse array of systems Peer learning focus. Direct insi ghts from practitioners, highlighting 'bumps in the road' and how to a void them. The Guide aims to provide an accessible operational resourc e to help practitioners put the market systems development approach in to practice. It explains the key principles and frameworks which guide the process of effective intervention in – and development of – marke t systems, addressing common challenges with examples of good practice based on practitioner experience. HOW SHOULD IT BE USED? The Guide ex plores, sequentially, the key elements of the implementation process: strategy, diagnosis, vision, intervention, measurement and management. It is not intended to be read from cover to cover; readers can go dir ectly to the chapter most relevant to their needs without having read preceding chapters. However each chapter does build upon the preceding one and may refer to other chapters. THE GUIDE IS STRUCTURED AS FOLLO WS: INTRODUCTION Overview of the objectives, structure and format of t he Guide CONTEXT A reminder of what market systems development means 1 . STRATEGY Core principles and framework for setting programme strateg y 2. DIAGNOSIS Core principles and framework for diagnosing system con straints 3. VISION Core principles and frameworks for defining and pla nning intervention 4. INTERVENTION Core principles and framework to gu ide effective intervention 5. MEASUREMENT Core principles and framewor k for measuring results 6. MANAGEMENT Key considerations in managing m arket systems development programmes GLOSSARY Definition of key terms used in market systems development